Friction Stir Welding and Processing VII - Mishra, Rajiv; Mahoney, Murray; Sato, Yutaka; Hovanski, Yuri.; Verma, Ravi.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This collection focuses on all aspects of science and technology related to friction stir welding and processing.
Keywords: Materials -- Analysis; Mechanical engineering; Materials; Characterization and Analytical Technique; Mechanical Engineering; Materials Engineering